PENGARUH PROJECT-BASED LEARNING TERHADAP KEMAMPUAN SAKUBUN MAHASISWA - Bayu Adinegoro; Yenny Aristia Nasution; Merri Silvia Basri (Jurnal Pendidikan Bahasa Jepang Undiksha, 2022)
Conventional writing learning is less able to improve students' abilities in developing their ideas because each student has different imaginations and interests. For this reason, in Sakubun learning one of the learning models that can be used to improve critical thinking skills and actively develop creative ideas is the project-based learning model. With a pure experimental method, research was conducted to analyze the differences in the results of the Sakubun learning before using the project-based learning model and after using the project-based learning model. The results of the paired t-test data analysis using SPSS 25, the 2-tailed significance value is 0.010 < 0.05, that there is a significant average difference between the pretest and posttest scores in the experimental class after using the project-based learning model, namely 57 to 74. The results of the essay also look more structured with detailed explanations. This proves that the project-based learning model can help students improve their pocketbook skills, especially in developing ideas.